The long term impact of an end-of-life communication intervention among Veterans with COPD - Reinke, Lynn F. (Heart Lung, 2017)
OBJECTIVE: The purpose of this study was to assess if an end-of-life communication intervention with patients with COPD led to higher long-term documentation of advance care planning discussions at the end-of-life. BACKGROUND: We previously demonstrated that providing clinicians a brief patient-specific feedback form about patients’ preferences for end-of-life communication improved the occurrence and quality of clinician communication about end-of-life care. METHODS: The study was conducted at the Puget Sound VA Healthcare System. Among those individuals enrolled in the intervention study (2004–2007) who had died during the follow-up period (up to 2013), we assessed if patients in the intervention arm had more goals of care discussions and formal advance directives completed as compared to patients in the control arm. We conducted logistic models accounting for provider level clustering, adjusting for age, FEV(1), and race. RESULTS: Among the 376 patients in the parent study, 157 died, of which 76 were in the intervention arm and 81 in the control arm. The mean age was 72.5 (SD 9.1), 99% were male, with a mean FEV(1)% predicted of 45 (SD 17.8). Over an average duration of 3.6 years (from the time of the first study appointment to death), 115 (73%) patients engaged in 451 unique end-of-life care discussions. The intervention was not associated with a higher percentage of patients with documented end-of-life conversations (I:C 75% vs 72%, p=0.63) or completion of advance care directives (26% vs 29%, p=0.55). CONCLUSIONS: Despite initially improving the occurrence of end-of-life conversations, the intervention did not increase the documentation of subsequent conversations about end-of-life care, nor did it improve documentation of advance directives. Seventy-five percent of the patients in our cohort had documented follow-up conversations showing most have these conversations, but there is room for improvement and an unclear impact on goal-concordant care. Future research should focus on testing multi-faceted, longitudinal, system-level interventions to enhance conversations about goals of care that promote goal-concurrent care.